ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT TERHADAP SIKLUS PENDAPATAN (STUDI KASUS PT. ASTRAGRAPHIA TBK) - Z, Zuliyanti; Putra, Rizki Eka; Jaya, Hendry (EQUILIBIRIA, 2015)
Zuliyanfi. Analysis of Accounting Information Systems Revenue Cycle Against Credit Sales at PT. Astragraphia Tbk Guided by In line with the development of information technology, the application of accounting information systems can support the lending process that is applied to Astragraphia Tbk PT. The research objective was to determine the accounting information system in which credit sales are effectively set by the company.The analytical method used is descriptive analysis method through a case study approach is a method that provides a systematic and accurate picture ofthe facts, and the nature of the relationship between the phenomenon under study in the company. Data was collected to achieve the goal is to conduct field research and library research. Fieldwork was obtained by interview and observation. While the research literature obtained from literature and books related to the researchconducted.From the analysis we concluded that the accounting information system of credit sales when viewed from the purpose of accounting information system is effective and can be said to be good because it is consistent with the theory that the accounting information system to support credit sales .. It can be seen from any part of the responsibility that has been carrying out their duties in accordance with the authority given, but the procedure of credit sales accounting information systems are used less effective, because there is a weakness and that is not a function of lack of credit, because the credit function held by the sales function